MENGEMBANGKAN KEMAMPUAN MEMBACA ANAK USIA DINI DENGAN MULTIMEDIA INTERAKTIF - PRIAWAN ARDI PUTRA (incrementapedia, 2020)
This research is motivated by the fact that learning still uses conventional learning. The media used is still using books or student worksheets. This causes teaching and learning activities for children to become bored and less varied. This is due to the lack of teacher media to convey learning to students. So that teachers prefer to use media that is easy and sober so that the development of children's reading skills has not yet developed optimally The aim of this research is to find out the effect of interactive multimedia on children's reading ability. The method used in this research is quantitative Pre Experimental with the design of "the one group pretest posttest". The sample in this study were 18 children in group A Kindergarten consisting of 10 male students and 8 female students. The data collection technique used is the method of observation and documentation. The results of the analysis show that the t test results Sig (0,000) <0.05 means there is an influence. This means that interactive multimedia affects the reading of group A children.